Learning Styles and Asynchronous Learning: Comparing the LASSI Model to Class Performance - Kenneth D. Loomis (Online Learning, 2019)
This study investigated the relationship between students’ individual study and learning styles with their performances in an online Research Methods class. At the beginning of the semester the Learning and Study Strategies Inventory (LASSI) measured each student’s study and learning styles on ten scales. The students’ LASSI scores were later correlated to their total class points, and grades on exams, projects, and assignments. Five of the LASSI scales had significant correlations with at least one aspect of the course assessment. The strongest correlation was found between time management skills and the final grade. The ability to effectively use study aids was significant in the students’ performance on the final grade, the final exam and all activities outside exams (journal reports and chapter assignments).